Piecewise linear aeroelastic rotor-tower models for efficient wind turbine simulations. Issue 4 (September 2020) - Macquart, T; Scott, S; Weaver, P M; Pirrera, A
Abstract: The development of software and methodologies able to efficiently and accurately predict the aeroelastic performance of wind turbines at low computational cost — enabling the rapid turnaround of novel concepts — is key to further reducing the levelised cost of energy. However, even the conventional low fidelity methods used for preliminary blade and rotor design are computationally expensive. The authors propose to improve the computational efficiency of dynamic aeroelastic time domain simulations by substituting conventional models with a piecewise linear aeroelastic rotor-tower model. This novel piecewise linear model is described and compared against standard modelling tools in this paper. Results suggest that piecewise linear rotor-tower models can be used to accurately capture the aeroelastic dynamic of wind turbine blades, with a significant (5 – 20×) reduction in computational costs.